A Rent-Protection Explanation for SEO Flotation-Method Choice. (13th July 2016) - Wu, Xueping; Wang, Zheng; Yao, Jun
Abstract: We model how a rent-protection motive drives the choice of flotation method in new equity issuance between two polar cases: rights issues and cash offers. Unexpected new blockholders would emerge in control-diluting cash offers and share in jealously guarded control benefits. But rights issues help the incumbent controlling shareholders avoid control dilution and safeguard their private benefits. Under asymmetric information about private benefits, the choice of flotation method can convey information about hidden private benefits and hence firm value. Our model can explain even a negative announcement effect of rights issues, and it supports not just one but three important equilibriums.